Firm-Specific Determinants of Productivity Gaps between East and West German Industrial Branches - Johannes Stephan; Karin Szalai (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2003)
Industrial productivity levels of formerly socialist economies in Central East Europe (including East Germany) are considerably lower than in the more mature Western economies. This research aims at assessing the reasons for lower productivities at the firm level: what are the firm-specific determinants of productivity gaps. To assess this, we have conducted an extensive field study and focussed on a selection of two important manufacturing industries, namely machinery manufacturers and furniture manufacturers, and on the construction industry. Using the data generated in field work, we test a set of determinant-candidates which were derived from theory and prior research in that topic. Our analysis uses the simplest version of the matched-pair approach, in which first hypothesis about relevant productivity level-determinants are tested. In a second step, positively tested hypothesis are further assessed in terms of whether they also constitute firm-specific determinants of the apparent gaps between the firms in our Eastern and such in our Western panels. Our results suggest that the quality of human capital plays an important role in all three industrial branches assessed. Amongst manufacturing firms, networking activities and the use of modern technologies for communication are important reasons for the lower levels of labour productivity in the East. The intensity of long-term strategic planning on behalf of the management turned out to be relevant only for machinery manufacturers. Product and process innovations unexpectedly exhibit an ambiguous picture, as did the extent of specialisation on a small number of products in the firms' portfolio and the intensity of competition.
urn:nbn:de:gbv:3:2-20518
Keywords: L6; M2; 330; productivity gap; East German industry; Produktivität; Unternehmen; Vergleich; Maschinenbau; Möbelindustrie; Bauwirtschaft; Schätzung; Neue Bundesländer; Alte Bundesländer